2020
DOI: 10.1039/d0tc01489c
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of Ru thin films using (2,4-dimethyloxopentadienyl)(ethylcyclopentadienyl)Ru and the effect of ammonia treatment during the deposition

Abstract: Ruthenium thin films were grown through atomic layer deposition using (2,4-dimethyloxopentadienyl)(ethylcyclopentadienyl)Ru [Rudense®] and oxygen at temperatures ranging from 250 °C to 270 °C and chamber pressures ranging from 0.5 Torr to 2.5 Torr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…This is because the ALD of Ru usually induces substrate-dependent nucleation delay, separate Ru island formation, and coalescence of islands into the continuous films, which results in high roughness. , For Ru applications as electrodes of the capacitors in the dynamic random access memory, the roughness of the Ru films should be as low as possible to avoid the reliability concerns of the adjacent dielectric thin films. Besides, the evolution of the surface roughness usually scales with the film thickness. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the ALD of Ru usually induces substrate-dependent nucleation delay, separate Ru island formation, and coalescence of islands into the continuous films, which results in high roughness. , For Ru applications as electrodes of the capacitors in the dynamic random access memory, the roughness of the Ru films should be as low as possible to avoid the reliability concerns of the adjacent dielectric thin films. Besides, the evolution of the surface roughness usually scales with the film thickness. , …”
Section: Introductionmentioning
confidence: 99%
“…Besides, the evolution of the surface roughness usually scales with the film thickness. 24,26 However, such a requirement of the smooth morphology of the Ru film may not be applicable when it comes to the electrode in RRAM. The high electrode roughness might even improve RS behavior.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Non-oxidative reactants such as NH3 are used in the in PE-ALD of transition metals. 36 With this in mind, the key advance of the current paper is to determine the reactions that take place during the metal precursor pulse in Ru ALD which then serves as a foundation for the ongoing investigation of the atomic level mechanism of the plasma pulse, similar to our earlier work 37 on Co precursor reactions.…”
mentioning
confidence: 98%
“…In the O 1s XP spectra in Figure 2(c), the O 1s peaks were detected under all conditions and were attributed to the oxidative reaction-based ALD process as well as an oxygen atom inside the Ru precursor. 25 In the case of the DFM-ALD condition, a considerable RuO 2 peak (529.5 eV) was detected, which was caused by the oxygen atoms in the surface region. In the case of the conventional ALD, a substantial surface contaminant (∼532 eV) peak was detected, which was related to water and hydrocarbons.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…Kwon et al reported that the surface morphology of Ru films could be improved by adopting an ammonia feeding/purge step during the Ru ALD process. 25 In the study, excessive RuO x layers, which play a crucial role in Ru precursor adsorption, could be reduced by an appropriate injection of ammonia gas. However, the strong reducing activity of ammonia gas deteriorated the interfacial region between the Ru film and the substrate.…”
Section: ■ Introductionmentioning
confidence: 99%